Analisis Faktor Perkembangan Kognitif dan Motivasi Belajar Mahasiswa - Romdah Romansyah (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to analyze the factors that influence cognitive development and the role of learning motivation in the learning process of teacher training students. Using a quantitative approach with a descriptive correlational design, this study involved 120 students from four study programs at the Faculty of Teacher Training and Education (FKIP) Galuh University, selected by purposive sampling from active students who regularly participate in lectures. The instruments used were a cognitive development questionnaire based on Piaget's theory and Bloom's taxonomy, and a learning motivation questionnaire with a Likert scale of 1–5. Data were analyzed using descriptive statistics, Pearson correlation, and simple and multiple linear regression. The results showed that cognitive development (β = 0.43, p < 0.01) and learning motivation (β = 0.37, p < 0.05) each had a significant influence on student achievement. A strong positive correlation between the two variables indicates a mutually supportive relationship. Academic environmental factors, independent learning strategies, and lecturer support were identified as the main drivers of cognitive development. These findings emphasize the need for higher education to integrate learning approaches that address students' cognitive development while simultaneously fostering intrinsic motivation to improve learning quality and future professional readiness.